PELUANG BISNIS USAHA KONVEKSI PAKAIAN DI KECAMATAN IV ANGKEK KABUPATEN AGAM - Yenni Del Rosa; Mohammad Abdilla (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2019)
This study explains the analysis of clothing convection business in the sub-district IV Angkek Agam regency, West Sumatra province, where the convection business is still unable to achieve optimal profit because it does not yet know what strategy to do. In this sub-district there are 8 clothing convection, 76 workers and an investment value of Rp. 589,200,000. Data was collected in a survey and structured interview on a sample of 8 pieces of convection (total sampling) while the data analysis was carried out qualitatively using a SWOT analysis. The stages of the clothing production business process are carried out through 8 stages, namely material preparation, pattern making, fabric cutting, application setting, application process, sewing, quality control and steam, packing. Based on the SWOT analysis it turns out to increase sales of clothing convection businesses in sub-districts IV Angkek Agam district must focus on implementing promotional strategies in various ways such as through social media facialbooks and Instagram, personal selling and public relations.Keywords: business convection, strategy and promotion